BULLYING AND PЕRSONAL DЕVЕLOPMЕNT: THЕ IMPACT OF BULLYING ON SЕLF-ЕSTЕЕM AND SЕLF-CONFIDЕNCЕ (TAMADDUN NURI JURNALI, 2025)
This article examines the impact of bullying on self-esteem and self-confidence. Bullying, which occurs in various forms (physical, verbal, social, cyberbullying), has a devastating impact on the mental health of the victim.